IMPLEMENTASI NILAI – NILAI DHARMASASTRA DALAM PENDIDIKAN AGAMA HINDU UNTUK MENGUATKAN KARAKTER SISWA - I Made Subagia Antara (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
This study aims to determine the implementation of Dharmasastra values in Hindu Religious Education to strengthen students’ character. This study used a qualitative approach with observation, interviews, and documentation as data collection techniques. Data were analyzed through data reduction, data presentation, and conclusion drawing.The results showed that Dharmasastra values were implemented through classroom learning, school culture habituation, religious activities, and teacher role modeling. The values applied included satya (honesty), ahimsa (non-violence), dama (self-control), guru bhakti (respect for teachers), and swadharma (responsibility). Teachers used contextual learning, habituation, moral reflection, and Balinese local culture in the learning process. The implementation of these values had a positive impact on students’ character, such as improving discipline, responsibility, honesty, self-control, and students’ spiritual and social awareness. However, the implementation also faced challenges from social media and digital culture. This study concludes that Dharmasastra values play an important role in strengthening students’ character and need to be implemented continuously through cooperation between schools, families, and communities.